Efektivitas Fogging dan Faktor Risiko Terhadap Kejadian DBD di Kelurahan Sungai Andai, Banjarmasin: - Agustina, Norsita; Suryanto, Deny; Ilmi, M. Bahrul; Rizal, Achmad; Jalpi, Agus; Anam, Khairul (Politeknik Kementerian Kesehatan Banjarmasin, 2025)
The working area of North Banjarmasin District includes 10 Banjarmasin sub-districts, including especially the Sungai Andai Health Center, which is one of the five main health centers in North Banjarmasin district. Based on data from the Banjarmasin City Health Office, in 2022 there were 5 cases of dengue patients, in 2023 there were 9 cases of dengue patients with a time span from January to April 2023. The purpose of this study is to determine the effectiveness of the use of fogging and risk factors for the incidence of dengue. This type of research is an analytical survey research using a cross sectional design. The population of this study is the entire community in Sungai Andai Village, which totals 9,172 heads of families in 2023. The sample of this study was 100 respondents by using accidental sampling, namely sample selection based on coincidence at the time of data collection. Test statistics using the Chi Square Test. The results of this study showed that there was a relationship between gender, mosquito repellent use, fogging and knowledge requests with the incidence of dengue (P-value < ( = 0.05). ) and there was no relationship between the use of mosquito nets and the incidence of dengue in the Sungai Andai Village Working area. It is recommended to the public to further increase efforts to eradicate mosquito nests (PSN) and monitor larvae regularly and thoroughly.